2008
DOI: 10.1211/jpp/60.10.0009
|View full text |Cite
|
Sign up to set email alerts
|

Bis(<I>α</I>-furancarboxylato)oxovanadium(IV) prevents and improves dexamethasone-induced insulin resistance in 3T3-L1 adipocytes

Abstract: Previous studies showed that bis(alpha-furancarboxylato)oxovanadium(IV) (BFOV), an orally active anti-diabetic organic vanadium complex, could improve insulin resistance in animals with type 2 diabetes. The present study has been carried out to evaluate the effects of BFOV on insulin-resistant glucose metabolism using dexamethasone-treated 3T3-L1 adipocytes as an in-vitro model of insulin resistance. The results showed that BFOV, similar to vanadyl sulfate and rosiglitazone, caused a concentration-dependent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Metal ions are known to often accelerate drug action, and the efficacy of a therapeutic agent may be enhanced upon coordination with a metal ion 20. Vanadium complexes show a variety of biological properties, and oxidovanadium(IV) complexes have been used to prevent and improve dexamethasone‐induced insulin resistance in 3T3‐L1 adipocytes 21. These compounds have also been used in receptor‐mediated signals22 and as anticancer agents 23,24.…”
Section: Introductionmentioning
confidence: 99%
“…Metal ions are known to often accelerate drug action, and the efficacy of a therapeutic agent may be enhanced upon coordination with a metal ion 20. Vanadium complexes show a variety of biological properties, and oxidovanadium(IV) complexes have been used to prevent and improve dexamethasone‐induced insulin resistance in 3T3‐L1 adipocytes 21. These compounds have also been used in receptor‐mediated signals22 and as anticancer agents 23,24.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, type 2 DM is characterized by peripherical IR, mainly in the liver, white adipose, and skeletal muscle tissues. There have been a few papers related to the investigation of vanadium compounds using IR models, high-fat diets, and synthetic glucocorticoids, which are the conditions that most represent type 2 diabetic patients [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, Barbera et al (2001) [ 20 ] showed that a treatment strategy based on the VOSO 4 did not block or attenuate DEXA-induced IR in rats. On the other hand, therapeutical strategies based on vanadium complexes are promising; for example, the use of the bis(alpha-furancarboxylato)oxidovanadium(IV) (BFOV) enhanced the action of insulin and completely prevented the development of insulin resistance induced by dexamethasone, modulating the gene expression of key proteins of the insulin cascade such as insulin receptor substrate 1 (IRS-1) and glucose transporter 4 (GLUT4) in 3T3-L1 adipocytes [ 19 ]. Although we have not yet clarified the molecular mechanism involved in the anti-IR of [V IV O(octd)] complex, it is reasonable to hypothesize that this vanadium-based compound activates the insulin pathway in metabolically important tissues such as the liver and skeletal muscle, which counteracts the anti-insulin effects of dexamethasone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,18 BFOV reduced FFA release from isolated rat adipocytes treated with epinephrine and enhanced the uptake of 2-deoxy-D-[ 3 H]-glucose in dexamethasoneinduced insulin resistance 3T3-L1 adipocyte. 19 Because the BFOV and metformin (Met) have different roles in regulating glucose homeostasis, including improving the insulin sensitivity of adipose tissue and reducing hepatic glucose production, respectively, we hypothesized the combination of these two agents would provide a combined effect on insulin resistance and related hepatic steatosis in a highfat diet-induced obese animal model. Therefore, the present study is the first to examine the effects of combination therapy with BFOV and Met on type 2 diabetes and hepatic steatosis in high-fat diet-induced obese C57 mice (HFC57 mice).…”
Section: Discussionmentioning
confidence: 99%